Identitas Digital dan Ekonomi Pesisir: Peran Instagram dalam Membentuk Praktik Sosial Pelaku Pariwisata di Pantai Pasir Panjang, Kepulauan Kei - Sapulette, Sacharias Izak; Haulussy, Rais Rahman (Universitas Pattimura, 2023)
This study aims to analyze the role of Instagram in shaping the social practices of local tourism actors at Pasir Panjang Beach, Kei Islands. The research focuses on how tourism stakeholders use Instagram as a medium to produce, distribute, and manage visual narratives about their destination. Employing a qualitative approach through digital observation, in-depth interviews, and content analysis, this study explores how visual representations on social media impact the formation of digital identity, strengthen social relations, and transform the economic strategies of coastal communities. The findings reveal that Instagram functions not only as a promotional tool but also as a symbolic space where tourism actors construct a collective self-image, expand social networks, and articulate economic aspirations grounded in local wisdom. This study offers a novel contribution by integrating theories of digital identity and economic sociology within the context of coastal tourism, an area that has received limited attention in global sociological literature. The findings recommend the development of digital literacy programs sensitive to local cultural contexts to support sustainable tourism practices and empower coastal communities in the digital economy era.